2017
DOI: 10.1073/pnas.1706255114
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of field experiments shows no change in racial discrimination in hiring over time

Abstract: This study investigates change over time in the level of hiring discrimination in US labor markets. We perform a meta-analysis of every available field experiment of hiring discrimination against African Americans or Latinos (n = 28). Together, these studies represent 55,842 applications submitted for 26,326 positions. We focus on trends since 1989 (n = 24 studies), when field experiments became more common and improved methodologically. Since 1989, whites receive on average 36% more callbacks than African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
393
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 613 publications
(461 citation statements)
references
References 25 publications
22
393
2
5
Order By: Relevance
“…Thus Zchirnt and Ruedin (), in their cross‐national meta‐analysis of post‐1990 field experiments, found no change in risks of discrimination in EU countries after the 2000 European directives on racial discrimination (2000/43/EC and 2000/78/EC). Quillian et al () found a similar lack of change over time in the US.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…Thus Zchirnt and Ruedin (), in their cross‐national meta‐analysis of post‐1990 field experiments, found no change in risks of discrimination in EU countries after the 2000 European directives on racial discrimination (2000/43/EC and 2000/78/EC). Quillian et al () found a similar lack of change over time in the US.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…In line with modern conceptualizations same of prejudice, attitudes toward outgroup members have become more positive over time, but behaviors toward outgroup members have remained largely unchanged (e.g., Quillian, Pager, Hexel, & Midtbøen, 2017). Avoidance of outgroup members (even when desire for intergroup contact is expressed; Shelton & Richeson, 2005) is the norm, segregation is common in settings such as cafeterias, beaches, and lectures (Clack, Dixon, & Tredoux, 2005;Dixon & Durrheim, 2003;Koen & Durrheim, 2010), and racial discrimination in hiring remains prevalent (Quillian et al, 2017). It appears that relative to negative intergroup attitudes, negative intergroup behaviors (e.g., avoidance; discrimination) are more persistent.…”
Section: Nt Er Gr Ou P Con Ta Ct a N D Be Ha V I Ormentioning
confidence: 81%
“…The liberal theory of stratification, which projects a benign future of widely shared opportunity and prosperity, remains the foil around which a great many contemporary analyses are still oriented (see Grusky and Hill ). Although the liberal theory dates back at least a half century (Blau and Duncan ), it remains to this day either an explicit or implicit backdrop to contemporary research on trends in social mobility (e.g., Pfeffer and Hertel ), gender inequality (e.g., Levanon and Grusky ), and racial and ethnic discrimination (e.g., Quillian, Pager, Hexel and Midtbøen ). In many cases, the liberal theory is used only to generate straw‐person hypotheses that can easily be disconfirmed, indeed it has arguably become our favourite foil.…”
mentioning
confidence: 99%